2021
DOI: 10.1177/2192568220974977
|View full text |Cite
|
Sign up to set email alerts
|

Bundled Payment Models in Spine Surgery

Abstract: Study Design: The following is a narrative discussion of bundled payments in spine surgery. Objective: The cost of healthcare in the United States has continued to increase. To lower the cost of healthcare, reimbursement models are being investigated as potential cost saving interventions by driving incentives and quality improvement in fields such a spine surgery. Methods: Narrative overview of literature pertaining to bundled payments in spine surgery synthesizing findings from computerized databases and aut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 44 publications
0
24
0
Order By: Relevance
“…In addition, hospital systems must evaluate risk allocation as repayment models are defined to avoid financially incentivizing doctors to select for only healthy patients with mild chronic conditions. Furthermore, moving to bundled payment may be complicated for practices that accommodate multiple payer types, as multiple eligibility requirements will have to be met and multiple provider-payer agreements will need to be forged (Heo et al, 2022;Hines et al, 2021;Hurh et al, 2017;Ryan et al, 2019;Stiegel et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, hospital systems must evaluate risk allocation as repayment models are defined to avoid financially incentivizing doctors to select for only healthy patients with mild chronic conditions. Furthermore, moving to bundled payment may be complicated for practices that accommodate multiple payer types, as multiple eligibility requirements will have to be met and multiple provider-payer agreements will need to be forged (Heo et al, 2022;Hines et al, 2021;Hurh et al, 2017;Ryan et al, 2019;Stiegel et al, 2021).…”
Section: Resultsmentioning
confidence: 99%
“…Spine surgery in particular shows higher fluctuations in profit/loss than other interventions ( Figure 9 ), as well as a higher cost weight with greater variability ( Figure 10 ). Indeed, Hines et al’s narrative review categorize spine patients as very heterogeneous with regard to surgery and postoperative outcomes [ 10 ]. They concluded that bundle payment systems could produce benefits in this surgery subtype, but should be stratified for risks and treatment costs.…”
Section: Discussionmentioning
confidence: 99%
“…One notable key to success is that price transparency can help leverage the direct knowledge of cost by incorporating equipment/implant procurement, information technology, labor, ancillary services, facility upkeep, and postacute care, to accurately record resource consumption, a process known as time-driven activity-based costing 20–22. Although this requires upfront investment and regular audit, practices will be in a position to maximize value of otherwise high-cost cases, offer greater price flexibility, and provide more accurate estimates for (bundled) price negotiations with insurers 23…”
Section: The Badmentioning
confidence: 99%
“…[20][21][22] Although this requires upfront investment and regular audit, practices will be in a position to maximize value of otherwise high-cost cases, offer greater price flexibility, and provide more accurate estimates for (bundled) price negotiations with insurers. 23…”
Section: Gaps In Disclosurementioning
confidence: 99%